Development of polycarbonate-silica matrix membrane for CO2/CH4 separation - Shafie, S.N.A.; Man, Z.; Idris, A. (American Institute of Physics Inc., 2017)
The high content of CO2 in CH4 can make the stream acidic. This will eventually have led to the corrosion of the pipelines. Among the various methods that have been discovered, polymeric membrane separation is among the most popular used in the industry. Polyamide and polyethersulfone are the conventionally used material for the polymeric membrane but they are expensive. Alternative material that is cheaper which is polycarbonate has been studied. The incorporation of silica nano-particles should give better result for the performance of the membrane. The preliminary results show that with the incorporation of silica nano-particles, the performance of the polycarbonate membrane increase in term of permeability and selectivity. © 2017 Author(s).